Occupant satisfaction towards public toilet at stadium in Terengganu / Muhammad Safwan Ramlan and Muhammad Zahir Zulkarnain - Ramlan, Muhammad Safwan; Zulkarnain, Muhammad Zahir (2023)
Public toilets are an integral part of stadiums, providing essential facilities for spectators. This research focuses on occupant satisfaction towards public toilets at stadiums in Terengganu, Malaysia. The visitors have high expectations for cleanliness and hygiene in the physical environment of stadiums, particularly regarding the sanitation and hygiene standards. The study examines factors such as cleanliness, comfort, and maintenance. Two stadiums, Sultan Mizan Zainal Abidin and Sultan Ismail Nasiruddin Shah Stadium, are considered as case studies. The researcher identifies several problems, including disrepair, lack of cleanliness, and inadequate ventilation. The findings indicate that a majority of respondents are satisfied with the cleanliness and environment of the toilets. However, a significant minority express dissatisfaction due to issues such as unhygienic conditions and inadequate facilities. This research contributes to enhancing the overall visitor experience by addressing the issues related to public toilets at stadiums in Terengganu.